PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN PENGUASAAN MATERI PADA PESERTA DIDIK KELAS XI SMA NEGERI 39 MALUKU TENGAH MATERI FLUIDA STATIS - Josipina. Kakerissa; H. Wenno; Jamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the increase in mastery of static fluid material after learning by applying the Problem Solving model to students of class XI IPA SMA Negeri 39 Central Maluku. This research is classified as a quasi-experimental type with a quantitative descriptive approach, with the research design used, namely One Group Pretest-Posttest Design. The sample used in this study were students of class XI IPA with a total of 13 students. The test instrument for the initial test and final test contains 11 essay questions and non-tests in the form of student worksheets (LKPD) to evaluate things on cognitive aspects during the learning process as well as increasing mastery of material using the normalized gain average. The results of this study indicate that in the initial test, 100% of students were in failing qualifications with an average achievement score of 9.84 with a score of 18.34 is the maximum achievement score and 4.58 is the minimum achievement score. The results of the analysis during the learning process using the problem solving learning model show that the average score of students' material mastery achievement is in good qualification with a score of 75.40. After learning, it shows a change in students' material mastery ability, where the average material mastery achievement score is in good qualification with an achievement score of 81.71 with a score of 88.07 is the maximum achievement score and 77.06 is the minimum achievement score. Meanwhile, for the N-Gain test results, a score of 0.79 was obtained which was in the high category. Thus, the application of the problem solving learning model as a learning model that can be used to improve mastery of static fluid material in class XI IPA students of SMA Negeri 39 Central Maluku.